Revolutionizing Banking Industry : The Role of Fintech in Modern Banking Industry - Heema Patadiya; Akshay Patel; Falguni Rahevar; Dr. Darshanaben Dipakkumar Pandya (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rise of Financial Technology (Fintech) is transforming the global financial ecosystem in significant ways. This project explores the growing impact of fintech on the banking industry, highlighting how technological innovations are reshaping traditional banking practices. The fusion of finance and digital technology has ushered in a new era of online and mobile banking, offering faster, more affordable, and more convenient financial services for both individuals and businesses. Fintech innovations—such as mobile wallets, contactless payments, peer-to-peer lending, blockchain platforms, and AI-powered financial advisors—are disrupting conventional banking frameworks. These tools not only improve user experiences through customization and instant access but also promote financial inclusion by serving previously unbanked or under banked populations.